Open innovation as a strategy for companies - Nguyen, Viet Hung; Špaček, Miroslav, 1954-; Mareš, Jan, 1986-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
Large service corporations struggle to keep pace with trends that bear the potentialof causing ruptures within the consulting industry to an unprecedented extend. Thegoal of the Master’s thesis was to prepare an open innovation strategy for aprofessional service company. Based on the conducted research and interviews withthe employees and external parties, the author suggested four main factors essentialfor the Open Innovation process and barriers that can limit the collaborationbetween the company and external participants in the innovation ecosystem. Theauthor suggested recommendation in each of the four defined factors. Lastly, theaim of the Master’s thesis was to encourage companies in the open culture anddemonstrate benefits from the external partnership with involved parties in theOpen Innovation initiative.
Vedoucí práce: Miroslav Špaček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses